143k views
4 votes
Find the standard form 3x=4y-4-2x -7=y2/3x-1/3y=2y=-3x+2x=-y-3

User Gavin Wood
by
4.7k points

1 Answer

7 votes

ANSWER:


\begin{gathered} 3x-4y=-4 \\ -2x-y=7 \\ 2x-y=6 \\ 3x+y=2 \\ x+y=-3 \end{gathered}

Explanation:

We have that the standard form of an equation is the following:


Ax+By=C

We have the following equations, we convert it into its standard form taking into account the above:


\begin{gathered} 3x=4y-4\rightarrow3x-4y=-4 \\ -2x-7=y\rightarrow-2x-y=7 \\ (2)/(3)x-(1)/(3)y=2\rightarrow2x-y=6 \\ y=-3x+2\rightarrow3x+y=2 \\ x=-y-3​\rightarrow x+y=-3 \end{gathered}

User Alain Gauthier
by
5.7k points